O “brincar e se-movimentar” como expressão fundamental para a curiosidade da criança - Souza, Cícera Andréia de (2015)
The main aim of this study is to analyze the curiosity in child’s life and highlight the importance of the “Play and Self-Move”, as its fundamental expression, for the promotion of it. To do this, we have as guidelines the Theoretical and Philosophical conception of Human Movement, also called “Self-Movement”, and studies on human curiosity. This is a theoretical research that was born of what it intends to study, that is, curiosity, because it can be said that the search for information or knowledge comes from the curiosity. We believe that the human being has a natural curiosity, although it stands out more on children, mainly through their spontaneous play. The Play and Self-Move is this spontaneous play, understood as the free Self-Movement covering games, drawings, dances, ultimately, the movement of the child in all its complexity that is a fertile ground for curiosity. As soon as we are born we are extremely curious individuals, our curiosity allows us to learn, and it happens initially through play. However, as we grow, we realize how much play is not valued and incorporated the belief that this activity is unnecessary except when it can bring positive results for the development of children. We are also led to stop making questions, another attitude of those who are curious, or doing it less, get used to the ready answers and have fake curiosities. In general, we fail to marvel at the world. This research aims to analyze the relation between child’s curiosity and the Play and Self-Move. We argue that, through physical education, kindergarten pedagogy and including the relationship of children with their parents and relatives, if based on this conception of movement and acknowledging the importance of curiosity and the Play and Self-Move, we can allow the development of large Existential fields, curiosity generators, making the child willing to learn more and thus contributing to the development and sustenance of curiosity for all child’s life.